Tutor Assistance in Increasing Citizens' Motivation to Learn in Night Class Learning - Yulianti, Yuli; Karwati, Lilis; Yuliani, Lulu (Indonesian Journal of Adult and Community Education, 2023)
This research was motivated by the lack of motivation of learning residents, boredom in participating in learning activities and the presence of learning residents who sometimes did not attend and were late for learning. The aim of this research is to determine tutor assistance in increasing students' motivation to study in evening class learning at PKBM Cerdik, Tasikmalaya City. The reason for conducting this research was because of the lack of motivation of residents to study package C in evening classes at PKBM Cerdik, Tasikmalaya City. The method used in this research is a qualitative approach with descriptive methods with data collection techniques, namely interview, observation and documentation techniques. Meanwhile, data analysis techniques are data reduction, data presentation, data verification and drawing conclusions. The research results obtained in this study are tutor assistance in increasing student motivation in evening class learning, namely tutors provide convenience in learning activities such as more flexible teaching methods for students, adapted to learning needs, learning methods and media are made in videos. learning, Power points and modules, as well as computer facilities to facilitate residents in taking part in night class learning as well as support from the environment and surrounding community, there is an increase in the motivation of residents to learn such as being able to use computers well, participating in learning well even though some residents' learning has not improved . The conclusion is that after participating in learning activities, students can get a job or be able to adapt to a better job. Earn sufficient income, have self-actuality and live a better life.